A Systematic Review of Law Enforcement Training Related to Autism Spectrum Disorder. (December 2020) - Railey, Kirsten S.; Love, Abigail M. A.; Campbell, Jonathan M.
Although research confirms the effectiveness of training to improve law enforcement officers' (LEOs) awareness and knowledge of people with intellectual disability and learning disabilities, review of the efficacy of autism-specific law enforcement training is needed. To provide up-to-date information regarding training for LEOs related to autism spectrum disorder (ASD), a systematic review of the literature was conducted. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Protocols (PRISMA), we conducted a search of 13 professional databases and 28 journals using search terms related to both ASD and law enforcement training. From 606 articles identified during the initial search, only two articles met inclusion criteria, which suggests that limited research exists that explores ASD and law enforcement training. Included studies were summarized in terms of participants as well as training format, content, and outcomes. Limitations of the current literature, directions for future research, and current implications for practice are discussed.